2002
DOI: 10.1074/jbc.m109616200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Mechanism of the Mg2+-dependent Nucleotidyl Transfer Catalyzed by T4 DNA and RNA Ligases

Abstract: The Mg 2؉ -dependent adenylylation of the T4 DNA and RNA ligases was studied in the absence of a DNA substrate using transient optical absorbance and fluorescence spectroscopy. The concentrations of Mg 2؉ , ATP, and pyrophosphate were systematically varied, and the results led to the conclusion that the nucleotidyl transfer proceeds according to a two-metal ion mechanism. According to this mechanism, only the di-magnesiumcoordinated form Mg 2 ATP 0 reacts with the enzyme forming the covalent complex E⅐AMP. DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
51
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 49 publications
5
51
0
Order By: Relevance
“…According to the model, the catalytic metal makes direct contacts with lysine-Nζ (the nucleophile) and with the α-β bridging oxygen of ATP (the leaving group) as two of the component ligands of an octahedral metal coordination complex that also includes four waters. The model does not mandate a direct contact between the metal and nonbridging ATP α-phosphate oxygens; instead the nonbridging phosphate oxygens are depicted as accepting hydrogen bonds from two of the metalbound waters (39). The NgrRnl structures presented here militate strenuously against such a model.…”
Section: Discussionmentioning
confidence: 99%
“…According to the model, the catalytic metal makes direct contacts with lysine-Nζ (the nucleophile) and with the α-β bridging oxygen of ATP (the leaving group) as two of the component ligands of an octahedral metal coordination complex that also includes four waters. The model does not mandate a direct contact between the metal and nonbridging ATP α-phosphate oxygens; instead the nonbridging phosphate oxygens are depicted as accepting hydrogen bonds from two of the metalbound waters (39). The NgrRnl structures presented here militate strenuously against such a model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on human RtcB and Archease suggest that Archease facilitates the guanylylation of RtcBq after a single turnover, enabling another round of catalysis . RtcB uses a two-manganese mechanism during catalysis (Desai et al 2013), which is analogous to the two-magnesium mechanism used by classical ligases (Cherepanov and de Vries 2002). The presence of an essential metal-binding site on the exterior of Archease at a tip, has led us to suggest that it might function to reach into and position Mn(II) ions within the RtcB active site.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleophilic attack on the ␣-phosphorus of ATP results in cleavage of the triphosphate moiety, formation of the enzyme-AMP -amino lysyl phosphoramidate, and release of the pyrophosphate (10). This reaction is reversible; we have shown that the dimagnesium ATP⅐Mg 2 form is the true substrate for the transfer of adenylyl moiety to the ligase (11). In the reverse reaction, DNA ligase uses the mono-magnesium form of pyrophosphate to synthesize ATP.…”
mentioning
confidence: 95%
“…In the stopped-flow instrument, this reaction is observed as a monophasic process with an activation energy of 16.2 kcal/mol (12). For T4 DNA ligase, ATP and pyrophosphate dissociation constants are Ͻ2 and 30 M, respectively (11). Thus, at the millimolar enzyme concentration used in this work, chemical equilibrium is shifted toward the protein-ligand complexes.…”
mentioning
confidence: 96%
See 1 more Smart Citation